Conventional Arms Control in the Baltic Sea: A Montreux for the North - William LIPPERT (Bulletin of "Carol I" National Defense University)
A conventional arms control (CAC) agreement for the Baltic Sea could help stabilize the security relationship, reduce arms racing, and improve diplomatic relations between Russia and the North Atlantic Treaty Organization (NATO). Similar to the Montreux Convention, which governs the passage of naval forces through the Turkish Straits, a CAC agreement focused on the Danish Straits could set limits on the size, type, number, and total tonnage of naval ships that pass through the straits. Additionally, or alternatively, an agreement could set limits on naval vessels based in the Baltic Sea, based on a combination of ratios, ship types, and capabilities. Any agreement could be implemented and managed by the state parties themselves or delegated to an agreement executor, such as an international organization.